Anti-inflammatory Effects of Fungal Metabolites in Mouse Intestine as Revealed by In vitro Models - Schreiber, Dominik; Marx, Lisa; Felix, Silke; Clasohm, Jasmin; Weyland, Maximilian; Schäfer, Maximilian; Klotz, Markus; Lilischkis, Rainer; Erkel, Gerhard; Schäfer, Karl-Herbert (Frontiers in Physiology, 2017)
Inflammatory bowel diseases (IBD), which include Crohn´s disease and ulcerative colitis, are chronic inflammatory disorders that can affect the whole gastrointestinal tract or the colonic mucosal layer. Current therapies aiming to suppress the exaggerated immune response in IBD largely rely on compounds with non-satisfying effects or side-effects. Therefore, new therapeutical options are needed. In the present study, we investigated the anti-inflammatory effects of the fungal metabolites, galiellalactone and dehydrocurvularin in both an in vitro intestinal inflammation model, as well as in isolated myenteric plexus and enterocyte cells. Administration of a pro-inflammatory cytokine mix through the mesenteric artery of intestinal segments caused an up-regulation of inflammatory marker genes. Treatment of the murine intestinal segments with galiellalactone or dehydrocurvularin by application through the mesenteric artery significantly prevented the expression of pro-inflammatory marker genes on the mRNA and the protein level. Comparable to the results in the perfused intestine model, treatment of primary enteric nervous system (ENS) cells from the murine intestine with the fungal compounds reduced expression of cytokines such as IL-6, TNF-α, IL-1β and inflammatory enzymes such as COX-2 and iNOS on mRNA and protein levels. Similar anti-inflammatory effects of the fungal metabolites were observed in the human colorectal adenocarcinoma cell line DLD-1 after stimulation with IFN-γ (10 ng/ml), TNF-α (10 ng/ml) and IL-1β (5 ng/ml). Our results show that the mesenterially perfused intestine model provides a reliable tool for the screening of new therapeutics with limited amounts of test compounds. Furthermore we could characterize the anti-inflammatory effects of two novel active compounds, galiellalactone and dehydrocurvularin which are interesting candidates for studies with chronic animal models of IBD.